PENGUJIAN TERHADAP NIAT MAHASISWA DIPLOMA III AKUNTANSI MENGIKUTI PELATIHAN BREVET PAJAK - Yanto Darmawan (Akademi Akuntansi YKPN Yogyakarta, 2019)
This research aims to investigate what factors that influence the intention of student of Diploma III in accounting to joining tax certification program. This research uses three constructs of the Theory of Planned Behavior namely the Attitudes Toward Behavior, the Subjective Norms and the Perceived Behavioral Control as a theoretical framework. Data was obtained through direct questionaires from 204 students of Akademi Akuntansi YKPN (AA YKPN) Yogyakarta. Data was analyzed by Structural Equation Modelling - Partial Least Square (PLS) using Smart PLS 2.0 software. The results of this research indicate that three constructs of TPB have significant influence on the student’s intention to joining tax certification program.